Role of Spatial Interpretations in Identity Imposing in Border Cities of EU-Russia - I. Yu. Okunev (Сравнительная политика, 2015)
Th e study shows how diff erent images of space on the same territory act as intermediate variables between objective territorial characteristics and citizens’ identities. As the geographical position at the border of Russia provides the citizens with geopolitical alternatives to identify their location as a fortress defending the nation (as in the case of Kronstadt) or a bridge between cultures, the given study allows us to compare reasons for these geopolitical choices of inhabitants.